Nosocomial Methemoglobinemia Resulting from Self-Administration of Benzocaine Spray - Christopher Hoffman; Hawa Abubakar; Pramood Kalikiri; Michael Green (Case Reports in Anesthesiology)
Methemoglobinemia is life-threatening and bears pathognomonic signs difficult to diagnose in real time. Local anesthetics are widely used and are known for eliciting this condition. We report a case of methemoglobinemia secondary to self-administered use of benzocaine spray. A 27-year-old woman was found to be in respiratory distress during postoperative recovery. After desaturation persisted, arterial blood gas yielded a methemoglobin level of 47%. The patient was successfully treated with intravenous methylene blue. Review of the events revealed self-administered doses of benzocaine spray to alleviate discomfort from a nasogastric tube. We review this case in detail in addition to discussing methemoglobinemia and its relevant biochemistry, pathophysiology, clinical presentation, and medical management. Given the recognized risk of methemoglobinemia associated with benzocaine use, we recommend its removal from the market in favor of safer alternatives.